THE STUDENTS’ MOTIVATION AND ACADEMIC ACHIEVEMENT AT TERTIARY LEVEL: A CORRELATIONAL STUDY - Eyin Tria Agustina; Achmad Yudi Wahyudin; Alfina Adelia Pratiwi (Faculty of Arts and Education, 2021)
One of the factors affecting student’s academic achievement is student learning motivation. The motivation that exists in students can drive them to be more enthusiastic to do excel in learning process. This study aimed to determine whether there is a correlation between the tertiary students’ motivation and the students’ academic achievement indicated by their Grade Point Average (GPA). This study was designed using a quantitative correlational study and 39 students were involved as the participant. Questionnaire and document perusal were done to collect the data. The results suggest that there is a positive correlation between students’ motivation and the students’ learning achievement.